Peran Motivasi Dalam Meningkatkan Kinerja Pegawai di Catatan Sipil Kota Palembang - Rusdi Rusdi (Jurnal Pemerintahan dan Politik, 2019)
AbstrackThe purpose of this study is to find out how the role of work motivation to improve the performance of civil service official officers and what factors affect the performance improvement of civil servant officials of Palembang city. The method used in this research is research method qualitative data analysis techniques. Data collection is done by conducting interviews with Key informants that have been established. The achievement of the company's goals depends not only on modern equipment, facilities and complete infrastructure, but more dependent on the people who carry out the work. The success of an organization is strongly influenced by the performance of individual employees. Each organization will always strive to improve the performance of employees, with the hope that what the purpose of the office will be achieved. In improving the performance of employees must take several ways such as through education, training, appropriate compensation, create a conducive working environment and not escape from the provision of good work motivation. While the factors that affect the improvement of employee performance is a complete adequate office facilities, work environment, and work priorities.Keywords : performance, civil service, motivation.AbstrakTujuan penelitian ini adalah untuk mengetahui bagaimana peran motivasi kerja untuk meningkatkan kinerja pegawai dinas sipil dan faktor-faktor apa yang mempengaruhi peningkatan kinerja pegawai negeri sipil kota Palembang. Metode yang digunakan dalam penelitian ini adalah metode penelitian teknik analisis data kualitatif. Pengumpulan data dilakukan dengan melakukan wawancara dengan informan kunci yang telah ditetapkan. Pencapaian tujuan perusahaan tidak hanya tergantung pada peralatan modern, fasilitas dan infrastruktur lengkap, tetapi lebih tergantung pada orang-orang yang melakukan pekerjaan. Keberhasilan suatu organisasi sangat dipengaruhi oleh kinerja masing-masing karyawan. Setiap organisasi akan selalu berusaha untuk meningkatkan kinerja karyawan, dengan harapan apa tujuan dari kantor akan tercapai. Dalam meningkatkan kinerja karyawan harus mengambil beberapa cara seperti melalui pendidikan, pelatihan, kompensasi yang sesuai, menciptakan lingkungan kerja yang kondusif dan tidak luput dari penyediaan motivasi kerja yang baik. Sedangkan faktor-faktor yang mempengaruhi peningkatan kinerja karyawan adalah fasilitas kantor yang lengkap memadai, lingkungan kerja, dan prioritas kerja. Kata kunci : kinerja, pegawai negeri, motivasi